IMPELEMENTASI KOMPETENSI PEDAGOGIK DALAM PENGUATAN KARAKTER PERCAYA DIRI MELALUI PEMBELAJARAN DARING - Choirul Ummami; Ujang Jamaludin; Encep Andriana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe the implementation of teacher pedagogical competence in reinforcing self-confidence through online learning to grade I students of SD IKS, Banten. The subjects of this study were class I teachers. The data collection techniques used by this researcher were through observation, interviews, and documentation. The observations were conducted in four meetings. The data analysis used in this research was descriptive qualitative. The results showed that the first-grade teachers of SD IKS had made efforts to implement pedagogical competencies in strengthening self-confidence. The teacher carried out strengthening self-confidence by including the cultivation of a confident character in every lesson plan (lesson plan) that the teacher made. In addition, strengthening the character of self-confidence in the online learning process was also carried out by applying the question and answer method, contextual and giving quizzes to students to spur students' selfconfidence. From strengthening the character of students' self-confidence, students were expected to be active, independent, and responsible.